The Attitude of Government-Based Development among Villagers and its Effects in Forming the Migration of Villagers to Cities (Case Study: of Cheshm-e Ali Akbar Village in Range of Selseleh City) - abouzar ghaseminezhad; seyed saeed vesali; behzad alizadeh (توسعه اجتماعی)
The purpose of this study which was conducted using qualitative method and interview and observation tools is that to what extent the attitude of government-based development was effective in forming of the migration of villagers to cities as the dominant model on rural development. The findings showed that the attitude of government-based development by creating the sense of dependence on government, making the spirit of consumerism, and changing the villagers to need-based people on one hand, Lack of comprehensive interest in villagers’ participation in rural development on the other hand, it leads the villagers to suffer from social and economic isolation that its Destructive effects can be seen in mitigation of villagers to cities. Whereas the people of Cheshm-e Ali Akbar was involved in determination of their destiny to the lowest extent, their trust particularly their institutional trust in government has been trimmed. Also, they lost their trust in meeting their ultra-need and earning a permanent income for future, its social damages are apparent in mitigation to cities.